Cyclophilin D: An Integrator of Mitochondrial Function - Amanakis, Georgios; Murphy, Elizabeth (Frontiers in Physiology, 2020)
Cyclophilin D (CypD) is a mitochondrial peptidyl-prolyl cis-trans isomerase, well known for regulating the mitochondrial permeability transition pore (PTP), a non-specific large conductance pore whose opening leads to cell death and has been implicated in ischemia/reperfusion injury in multiple organs, in neurodegenerative disorders and in muscular dystrophies. While the main target of CypD is a matter of ongoing research, inhibiting CypD protects in models of those diseases making it an interesting therapeutic target. The present review focuses on post-translational modifications of CypD that have been identified by recent studies, which can alter the regulation of the PTP, and contribute to understanding the mechanisms of action of CypD.